The hurricane sisters [large type] : a novel - Frank, Dorothea Benton (HarperLuxe, an imprint of HarperCollinsPublishers, 2014)
"Matriarch, Maisie Pringle, is a force to be reckoned with. Her daughter, Liz, is caught up in the classic maelstrom of middle age. And Liz's beautiful twenty-something daughter, Ashley, and her dreamy ambitions for the future keep them all at odds"--Page 4 of cover.